The politics of peace : Ephesians, Dio Chrysostom, and the Confucian Four books - Lau, Te-Li. (Novum Testamentum, Supplements, 2010)
Although scholarship has noted the thematic importance of peace in Ephesians, few have examined its political character in a sustained manner throughout the entire letter. This book addresses this lacuna, comparing Ephesians with Colossians, Greek political texts, Dio Chrysostom's Orations , and the Confucian Four Books in order to ascertain the rhetorical and political nature of its topos of peace. Through comparison with analogous documents both within and without its cultural milieu, this study shows that Ephesians can be read as a politico-religious letter "concerning peace" within the church. Its vision of peace contains common political elements (such as moral education, household management, communal stability, a universal humanity, and war) that are subsumed under the controlling rubric of the unity and cosmic summing up of all things in Christ.